Redo aortic root surgery post-Ross procedure - Bogachev-Prokophiev, Alexander; Sharifulin, Ravil; Demin, Igor; Karadzha, Anastasiia; Zheleznev, Sergey; Karaskov, Alexander; Afanasyev, Alexander; Pivkin, Alexey; Ovcharov, Mikhail; Zalesov, Anton; Murashov, Ivan; Tsaroev, Bashir; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Despite numerous advantages of the Ross procedure, it presents a risk of late autograft and right ventricular outflow tract conduit failure. This study aimed to analyze the outcomes of autograft dysfunction reoperations using autograft-sparing and root replacement techniques. Methods Between 2015 and 2023, 49 patients underwent redo root surgery in our institution. Autograft valve-sparing procedures (VSP) were performed in 20 cases and the Bentall procedure (BP) in 29 patients. The short and long-term clinical outcomes along with echocardiographic results of VSP and BP were investigated. Results Overall early mortality rate was 2.0% with no significant difference between the groups. Severe autograft valve insufficiency at the time of redo (OR 4.07, P = 0.03) and patient age (OR 1.07, P = 0.04) were associated with a valve replacement procedure instead of VSP. The median follow-up duration was 34 months. No late deaths occurred in either group. Freedom from VSP failure and aortic prosthesis dysfunction were 93.8% and 94.1% in the VSP and BP groups, respectively. No reoperations were necessary in either group. Conclusion Redo aortic root surgery can be safely performed in patients with autograft failure. Both root replacement and autograft valve-sparing procedures demonstrated acceptable results at mid-term follow-up. Early redo surgery pre-empting severe aortic insufficiency increases the likelihood of preservation of the dilated autograft valve.